Utilization of Contraception Among Women of Reproductive Age in Ajman, UAE - Hemanth, Navana; Saifa, Musamat U; Ashik, Ashiba; Sherif, Mehrin; Muttappallymyalil, Jayakumary (International Journal of Innovative Research in Medical Science, 2023)
This study was conducted to determine the contraception utilization pattern and to assess the factors influencing contraceptive utilization among women in the reproductive age group in Ajman, UAE. This cross-sectional study was conducted in April 2022. A total of 209 participants were recruited from University Hospital, shopping malls, and residential areas in Ajman. An interviewer-administered validated questionnaire was used for data collection. The domains covered include Socio-demographic profile, Reproductive history, Utilization pattern, and Factors influencing the choice and discontinuation of contraception. Participants were women in the reproductive age group (18-44 years), of any nationality and those who consented to participate in the research. Collected data was entered into an Excel spreadsheet and transferred to SPSS version 28 for analysis. Descriptive statistics was used to describe the study population. The chi-square test was used to test the association between independent variables and dependent variables (choice, use, and discontinuation). The p-value was set at ≤ 0.05 which is considered statistically significant. Out of 209 women interviewed, only 53.1% utilized contraception to limit family size. Participants who considered their partner’s wishes as very important refrained from using contraceptives (42, 80.8%). Cultural background had a major negative influence which led participants to avoid contraceptive use (37, 72.5%). with regard to participant’s education, there is a contrast between the usage of contraception among individuals with an education above the undergraduate level (53;31.3%) and below (11;27.5%). Participants with husbands who received an education above undergraduate level (36;26.3%) showed limited usage of contraception as compared to those less than undergraduate (13;39.4%). To conclude the prevalence of utilization of contraception was 53.1%. The nationality of the participants and husband's education was highly associated with contraceptive use. The number of previous live births also determined the use of contraceptives. Healthcare professionals especially doctors played a pivotal role in spreading awareness about contraception and newer forms of contraceptives. Along with complications in the previous pregnancy, Influence from both partner and family leading to discontinuation of contraceptives also had a major impact. The belief among participants that contraception influences hormones was a factor that impacted the usage of contraception.